'Delete the family': platform families and the colonisation of the smart home. Issue 7 (19th May 2021) - Goulden, Murray
ABSTRACT: On its surface, the 'smart home' marks an effort to augment everyday domestic life to the benefit of its members, through the pervasive digital technologies of the Internet of Things (IoT). Through an analysis of the family-imitating group accounts offered by both Google and Amazon, as part of their smart home ecosystems, this paper identifies a project of constructing a new site for platform capitalism, in the form of the platform family, and its effort to pacify domestic life. The platform family is an engineered simulacra of domesticity, formatted to run on the smart home operating system, serving simultaneously as a vehicle for domestic consumption, and a vehicle for consuming domestic life. Drawing on sociology of the family, we contextualise this by showing how the home has long been a site of struggles between internal and external control. Addressing the reconfiguration of membership possibilities within the platform family, we show how it seeks to intervene in domestic life, by reshaping family's material possibilities and normativities. Looking past the technologies to the social forms they imbue reveals a project that is ultimately motivated by a desire to colonise the home as a site for platform capitalism. We conclude by highlighting the potential for resistance in this space and ask whether the homogenisation of domestic life attempted by these interventions is not fundamentally contradictory, in denying the very qualities that give family its value.